2019
DOI: 10.18176/jiaci.0369
|View full text |Cite
|
Sign up to set email alerts
|

The –2549 –2567 del18 Polymorphism in VEGF and Irreversible Bronchoconstriction in Asthmatics

Abstract: Background: While the importance of vascular endothelial growth factor (VEGF) in the pathogenesis of several diseases (eg, neoplasms) has been proven, its role in asthma, especially in terms of the potential associations between genetic variants of VEGF and airway remodeling, has received relatively little attention. Objectives: This study aimed to evaluate the possible connection between a genetic factor, ie, the polymorphism del/ins in the VEGF promoter region, and airway remodeling potential in asthmatics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Genetic factors play pertinent roles in the morbidity and mortality of diseases. It was reported that SNPs in the VEGFA gene were associated with lung diseases such as COPD, asthma, lung cancer and acute respiratory distress syndrome (Gomulka et al, 2019;Hernandez-Pacheco et al, 2018;Yu et al, 2017;Zhao et al, 2020). Our study analysed five SNPs (rs833068, rs833070, rs3024994, rs3024997 and rs3025000) of VEGFA and found that some of them may play a vital role in the occurrence and development of COPD.…”
Section: Discussionmentioning
confidence: 77%
“…Genetic factors play pertinent roles in the morbidity and mortality of diseases. It was reported that SNPs in the VEGFA gene were associated with lung diseases such as COPD, asthma, lung cancer and acute respiratory distress syndrome (Gomulka et al, 2019;Hernandez-Pacheco et al, 2018;Yu et al, 2017;Zhao et al, 2020). Our study analysed five SNPs (rs833068, rs833070, rs3024994, rs3024997 and rs3025000) of VEGFA and found that some of them may play a vital role in the occurrence and development of COPD.…”
Section: Discussionmentioning
confidence: 77%
“…A third line of contribution to protection or increased risk of developing atopic conditions is the genetic background. As an example, a del/del genotype (−2549 −2567 del18) of Vascular Endothelial Growth Factor (VEGF) has been associated with asthma occurrence and irreversible bronchoconstriction [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other papers [ 24 , 25 ], matters of basophils VEGF-activation and the potential contribution of VEGF gene polymorphism to the spontaneous increase of eosinophils activity (priming) in patients with asthma were suggested. Also, the genetic variant such as the del18 genotype in the promoter region of the VEGF gene was demonstrated as a possible factor connected with presence of and the risk of irreversible bronchoconstriction in asthmatics [ 26 ]. Interestingly, the above might indicate the influence of VEGF and its genetic region on different cell activation state in asthmatics.…”
Section: Discussionmentioning
confidence: 99%